MANAJEMEN LABA PADA PERUSAHAAN KELUARGA BIDANG MANUFAKTUR - Titi Purbo Sari; Nasron Alfianto; Nurul Juwariyah (Jurnal Akuntansi dan Bisnis, 2024)
Most companies in Indonesia are managed by family business groups. Family businesses provide opportunities for owners who own majority shares to control the company and influence management in the decision-making process, including gaining personal benefits through earnings management practices. The purpose of this study was to prove the effect of family control on earnings management actions in the manufacturing industry. Sample selection was based on the purposive sampling method. The sample used in this study was family companies in the manufacturing industry listed on the Indonesia Stock Exchange for the 2017-2019 period totaling 477 companies, but the samples that met the criteria were 298 companies. The data were processed and analyzed using multiple regression methods. The results of this study include, the independent variables, namely family ownership and family members, do not affect earnings management actions, while the control variable, namely leverage, has a negative and significant effect on earnings management, and company size does not affect earnings management